(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The article analyzes changes in indicators of the state of physical health of student youth in the period 2016-2023. The total number of subjects (n=688). The goal is to conduct a comparative analysis of the results of monitoring the physical health of students of the Khmelnytskyi Humanitarian and Pedagogical Academy after two years of distance learning. Research methods included: analysis of scientific and methodical sources; poll; survey; pedagogical observation; methods of studying indicators of anthropometric, functional and morphofunctional state of health of students; comparative analysis; methods of mathematical statistics. New technologies of physical education that appeared in the period of distance education were based on the creation of innovative training and led to the emergence of a concept based on the conscious and active participation of students in independent physical improvement under the guidance of a teacher. The results of the study showed that changes in anthropometric, functional and morphofunctional health indicators of students occurred during two years of distance learning in physical education. They indicate the appearance of excess weight, deterioration of cardiovascular and respiratory system performance, and a decrease in the level of work capacity of student youth. During the period of distance learning in physical education, the negative trends in the deterioration of indicators of the state of physical health of students accelerated twice. Conclusions. The general trends of a decrease in the level of physical activity and the state of health of student youth worsened due to the introduction of quarantine restrictions caused by the COVID-19 pandemic in 2020 and from 2022 the introduction of martial law in Ukraine, which forced higher education institutions to switch to distance education. The implemented technologies of distance learning in the physical education of students allowed only to partially solve the problems of compensating for the low motor activity of young people. The insufficient level of motor activity of students and their sedentary lifestyle negatively affected the general state of their physical health. The most effective means of improving the health indicators of student youth are purposeful, personally significant, systematic physical exercises.